2019
DOI: 10.31436/iiumej.v20i2.912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bonded Composite Patch on the Stress Intensity Factors for a Center-Cracked Plate

Abstract: Crack propagation until fracture is an important criterion to predict a structure‘s service life. In order to increase the latter, the cracked component needs to be repaired or replaced. In the present study, a finite element analysis has been carried out to investigate the effects of adhesive thickness, patch thickness and crack length on the passive repair performance of a center-cracked rectangular aluminum plate under mode-I loading condition using an ANSYS package. A comprehensive parametric study shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…31 For instance, thicker patches will lead to higher failure loads. 32,33 Upon investigating the failure surfaces for repaired samples, similar failure modes were generally observed for both repair methods, explaining the similar strength values presented in Figure 13. TW specimens repaired by US consolidation and vacuum bagging shown in Figure 14(a) and (b), and PW vacuum-bagged specimens shown in Figure 14(f), characteristically failed by net tension failure.…”
Section: Mechanical Testingsupporting
confidence: 62%
See 1 more Smart Citation
“…31 For instance, thicker patches will lead to higher failure loads. 32,33 Upon investigating the failure surfaces for repaired samples, similar failure modes were generally observed for both repair methods, explaining the similar strength values presented in Figure 13. TW specimens repaired by US consolidation and vacuum bagging shown in Figure 14(a) and (b), and PW vacuum-bagged specimens shown in Figure 14(f), characteristically failed by net tension failure.…”
Section: Mechanical Testingsupporting
confidence: 62%
“…31 For instance, thicker patches will lead to higher failure loads. 32,33
Figure 13.Strength of open-hole and repaired samples from configuration shown in Figure 5 for UD, PW, and TW laminates. For the unnotched UD sample, strength value was taken from the material's technical data sheet.
…”
Section: Resultsmentioning
confidence: 99%
“…This means the shear stress transfer from the patch to the damaged plate is high and bonding is strong when it is thinner. Indeed, previously, it has been recommended that the adhesive thickness provide a higher reduction in SIF when it is thinner or between 0.25 mm to 0.35 mm [ 30 ]. Whenever the thickness of the adhesive bond increases, a small reduction is found in the NSIF.…”
Section: Resultsmentioning
confidence: 99%
“…In recent investigations on the bonded composite repair of damaged structures, numerous studies have reported using the FE method [ 23 , 24 , 25 ] and experimental work [ 26 ] compared with analytical work. Additionally, the stress concentration factor (SCF) has played an important role in fracture parameters, and it has been reduced using a bonded composite patch with the same FE method [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%